The Development of a Questionnaire to Measure Achievement Motivation in Physics Education Student - Faresta, Rangga Alif; Kosim, Kosim; Gunawan, Gunawan; Taufik, Muhammad (Indonesian Publication Center, 2020)
Achievement motivation is part of the affective domain which also determines learning success. Motivation is an incentive for individuals to do better and tends to assess themselves to measure the progress that has been achieved. Researchers intend to conduct development research to produce appropriate achievement motivation instruments. So that it can be used as an instrument for evaluating achievement motivation in students. This research is a research and development (R&D) with 4D model namely Define, Design, Develop and Disseminate. In this study, only the develop phase was carried out, namely expert validation and limited trials. The instrument developed was a questionnaire with 4 Likert scales. The sample used was Physics Education students at FKIP Mataram University. From the results of the study note that as many as 74% of students who have high motivation, and as many as 11% of students who have moderate motivation. For the results of the feasibility analysis, achievement motivation was obtained from the results of the validator assessment. Based on the validator's evaluation, the achievement motivation questionnaire has an average eligibility of all aspects of 3.37 with a very good category and a content validation value of 0.85 with a valid category. So it can be concluded if the achievement motivation evaluation instrument is appropriate to be used in the assessment of achievement motivation in students.